Dynamics of pomegranate fruit weight loss during precooling and ambient storage: a spatial and temporal analysis - Mukama, M.; Ambaw, A.; Opara, U. L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
In this paper the spatiotemporal profile of weight loss of pomegranate fruit (cv. Wonderful) was investigated during precooling and simulated shelf conditions. The effects of relative humidity (RH) inside the cold room, polyliner inside the packaging and stack orientation on fruit weight loss were studied. Weight loss during the precooling operation ranged from 0.17 to 0.25% of the initial fruit weight and was highest during precooling of stack without liner and inside non-humidified room (0.25%). It was observed that fruit weight loss in liner-based packaging was almost equivalent to room humidification. Results of the shelf life study demonstrated the importance of room humidification to preserve fruit quality. Storing fruit in a room at 95% RH minimised weight loss and best maintained fruit colour, firmness, size and chemical quality attributes of pomegranates. On the other hand, fruit stored at ambient condition (65% RH) up to 30 days had excessive weight loss (up that 29.13±1.49%), which led to shrivel, deformed appearance and considerably reduced overall visual quality.